ANALYSIS OF THE CURRENT STATE AND THE DYNAMICS OF LIPID-LOWERING DRUGS IN THE PHARMACEUTICAL MARKET OF UKRAINE - Alla A, Kotvitska; Alina V, Cherkashyna; Alina V, Volkova; Inna V, Kubarieva (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The purpose of this study was to analyze the assortment, availability, consumption status, and dynamics of lipid-lowering drugs in the pharmaceutical market in Ukraine. Methods: Among the primary methods of research were applied the following: System and content analysis, marketing, logical and mathematical analysis, graphical mode, and also a way of detailed and abstract simulation and synthesis. Results: The ratio of imported and domestic lipid-lowering drugs in Ukrainian pharmaceutical market was analyzed (imported lipid-lowering medicines account for 82% of the total number of this group in Ukrainian market, the share of local medications is 18%, respectively). The structural review and analysis of market characteristics of 5-hydroxy-3-methylglutaryl-coenzyme A reductase inhibitors group of medicines (sales, accessibility for people, and competitiveness) were conducted, and the most promising market segment for producers and distributors was identified. The most promising sector is rosuvastatin, which is characterized by an average sales volume with a tendency to increase and a high increasing profit. Conclusion: Data on dynamics of the development of lipid-lowering drugs segment in the pharmaceutical market of Ukraine are systematized, which enables potential manufacturers to identify their market niche. As a result of the study, heavy dependency on imported lipid-lowering drugs in the pharmaceutical market of Ukraine was established, which determines low economic accessibility (especially in case of increasing in exchange rates) and physical availability (dependence on the regularity of shipments to Ukraine) for consumers. The most competitive medicines of atorvastatin and rosuvastatin group were determined, it was established that sales leader was pharmaceutical company KRKA dd, Novo Mesto (Slovenia) with generics Atoris and Roxer.